(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Gimnatika exercises, jump, balance to maintain, twist, shake the bottle, without the product, the parts with, direction and to relax navbatlashtirish with, the same with along the base in front of the exercise of their into gets and gavin, the hands, leg muscle-the world will strengthen. They not only power and joints mobility , you will develop not, the muscles in subtle sensations, movement of the koordinatsiya up, on qaddi body shape, difficult conditions in a balance and keep, so help willgan exercise will ketmaketlik and them about the concepts given.